A Microchip Integrated Sensor for the Monitoring of High Concentration Photo-voltaic Solar Modules. (2016) - Corte, F.G. Della; Cocorullo, G.; Corsonello, P.; Felini, C.; Merenda, M.; Perri, S.; Borelli, G.; Carpanelli, M.; Verdilio, D.
Abstract: A CMOS sensor fabricated in 0.35μm technology, specifically designed for the monitoring of High Concentration Photo-Voltaic (HCPV) modules, is presented. The microchip was designed to monitor temperature and illumination of each solar cell in a module. Temperature is measured by monitoring the base-emitter voltage of two coupled, diode connected, bipolar transistors, while the illumination sensor is an integrated p-n junction photodiode. A custom communication protocol is implemented in the chip to allow the sharing of a two-wire communication resource among the cells.